2013
DOI: 10.1139/apnm-2012-0490
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofLactobacillus gasseriOLL2809 and α-lactalbumin on university-student athletes: a randomized, double-blind, placebo-controlled clinical trial

Abstract: Strenuous exercise reduces immune cell function and increases the risk of respiratory and gastrointestinal infections. In addition, it affects mood state and causes physical fatigue. Athletes require both mental and physical conditioning to execute good performance. In this study, we conducted a randomized, double-blind, placebo-controlled clinical trial to evaluate the immunopotentiation and fatigue-alleviation effects of Lactobacillus gasseri OLL2809 (LG2809) and α-lactalbumin (αLA) in university-student ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…The sample size was estimated referring to previous research such as Kelly et al [31], and Sashihara et al [32] which are similar to the present study. In the study conducted by Allen et al [33], stated that to achieve 80% power for a one-way ANOVA, a minimum sample size of 20 was required to demonstrate an effect size of 0.3 at the significance level of 0.05.…”
Section: F Sample Size Estimationmentioning
confidence: 76%
See 1 more Smart Citation
“…The sample size was estimated referring to previous research such as Kelly et al [31], and Sashihara et al [32] which are similar to the present study. In the study conducted by Allen et al [33], stated that to achieve 80% power for a one-way ANOVA, a minimum sample size of 20 was required to demonstrate an effect size of 0.3 at the significance level of 0.05.…”
Section: F Sample Size Estimationmentioning
confidence: 76%
“…A study conducted by Yang [38] with laryngeal cancer patients, the anxiety level of the patients were lowered significantly before the surgery after exposed to two weeks of probiotic supplementation. Another study conducted by Sashihara [32] using university athletes who daily undergone strenuous training showed significant decrement of tension anxiety scores in profiling mood states (POMS). Furthermore, Rao [39], conducted a study to find the effect of probiotics on anxiety and depression using chronic fatigue syndrome patients and results were significantly lowered after 8 weeks similar to the present study.…”
Section: Anthropometric Body Composition Measurementsmentioning
confidence: 99%
“…Supplementation of L. gasseri improved mood (Sashihara et al, 2013) and depressive-like symptoms in stressed individuals. However, no studies have evaluated the effect of L. gasseri on clinically depressed individuals.…”
Section: Lactobacillus Gasserimentioning
confidence: 93%
“…Two weeks post-examination, the probiotic group showed significantly higher faecal serotonin, though the psychological implications of this change are less clear. Another study found that, relative to placebo, student athletes ( n  = 44) fed Lactobacillus gasseri OLL2809 LG2809 showed elevated mood and reduced natural killer cell activity after strenuous exercise, with some additional alleviation of fatigue when the probiotic was consumed alongside α-lactalbumin [37]. These results suggest that probiotics may have ecologically relevant benefits and the potential to enhance performance on some important life activities.…”
Section: Human Researchmentioning
confidence: 99%